Accurate proportional power sharing with minimum communication requirements for inverter-based islanded microgrids. (October 2020) - Macana, Carlos A.; Mojica-Nava, Eduardo; Pota, Hemanshu R.; Guerrero, Josep; Vasquez, Juan C.
Highlights: A novel power sharing control approach for accurate proportional active and reactive is proposed. Fast transient response, adequate frequency regulation, and minimum communication requirements are achieved. The controller performance is evaluated experimentally under several load and generation scenarios. The control approach tolerates constant communication time-delays of 200 ms and multiple communication failures. Abstract: The proportional power sharing is essential to guarantee reliability on the operation of an islanded microgrid. However, inaccurate reactive power sharing in scenarios with line impedance mismatches, and slow transient response remains important limitations of most of the conventional power sharing controllers. In this work, a novel method for power sharing control based on a decentralized Direct Current Primary Controller (DCPC) and a distributed Consensus-based Quadrature Current Controller (CQCC) is proposed. The main properties of the control approach are shown including accurate proportional active and reactive power sharing under mismatched feeder impedances and frequency regulation characteristics. Faster transient response, power sharing accuracy and minimum communication requirements are the advantages of the proposed method. The controller properties, the impact of constant communication time delays and communication failures on the power sharing performance are evaluated on different experimental study cases. These experimental results show that the accurate power sharing state is achieved in less than 2 s with frequency deviations lower than 40 mHz in all the study cases. Additionally, it is shown that the control approach tolerates constant communication time-delay of more than 200 ms and multiple communication failures that maintains the connectivity properties on the communication graph.